The effect of online learning quality on vocational students' learning achievement during the Covid-19 Pandemic - Feri Ferdian; Hijriyantomi Suyuthie (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
This study aimed to analyze the effect of online learning quality on vocational students' learning achievement during the Covid-19 pandemic. This type of research uses a quantitative approach with ex post facto research, which aims to analyze exogenous variables (online learning quality) with endogenous variables (vocational students' learning achievement during the Covid-19 pandemic). The population of this study was 198 vocational students in the hotel management program Universitas Negeri Padang who took the front office operations two courses in the semester of January-June 2021. The sampling technique used in this study is total sampling. The number of successfully collected respondents was 174 people (87,9%). The data analysis technique used is simple linear regression analysis. The results showed that: (1) Online learning quality during the Covid-19 pandemic is a sufficient category, (2) Vocational students' learning achievements during the Covid-19 Pandemic are also in a good category, and (3) There is a significant influence on the online learning quality variable on the vocational students' learning Achievement during the Covid-19 Pandemic. The magnitude of the online learning quality variable's influence on the vocational students' learning achievement during the Covid-19 Pandemic is 2.7%, while other factors determine 97.3%. This finding also provides a basis for other researchers to look at and have a wider scope, especially those related to student learning achievement. Vocational programs in universities must design an attractive learning process development program for students while still paying attention to the quality of the learning process. This form of practical implication will encourage students to be more motivated to study well so that their learning achievement can be obtained as expected.